STUDENTS’ ATTITUDE TOWARDS LEARNING ENGLISH - Djamil, Ewieth Citra Amalia; Badu, Helena; KaU, Magvirah El Walidayni (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2017)
Having a positive attitude towards learning English does not always appear in students’ behavior. Kara (2009) states that attitudes towards learning influence students’ behaviors and consequently on their performance. In investigating the students’ attitude, this study applies questionnaire which is grounded in the theory of attitude’s component and attitude in learning. The result shows that there are positive and negative attitudes among the students of English Department, specifically in term of affective, behavioral and cognitive components. The positive attitude is signed by the students’ enthusiasm and ambition in the learning process whereas the negatives are indicated by the lack of those two aspects. The result of this research can help teachers to recognize the students’ attitudes. Hence the teachers can maximize their teaching performance and develop new techniques of teaching English to make the students interested in English learning process